1994
DOI: 10.1128/iai.62.8.3058-3065.1994
|View full text |Cite
|
Sign up to set email alerts
|

Specific genetic variants of Actinobacillus actinomycetemcomitans correlate with disease and health in a regional population of families with localized juvenile periodontitis

Abstract: A geographically homogeneous population of 83 subjects, from 21 families with localized juvenile periodontitis (IJP), and 35 healthy control subjects was monitored, over a 5-year period, for the presence of the periodontal pathogen ActinobaciUlus actinomycetemcomitans. Restriction fragment length polymorphism (RFLP) analysis was used to monitor the distribution of genetic variants of this bacterium in UJP-susceptible subjects that converted from a healthy to a diseased periodontal status. A. actinomycetemcomit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 23 publications
(26 reference statements)
1
71
0
2
Order By: Relevance
“…a particular clone, termed JP2, of Aggregatibacter [formerly Actinobacillus (Nørskov-Lauritsen & ] actinomycetemcomitans which, like traditional pathogens, may be isolated from multiple patients in geographically distinct areas (Haubek et al, 2008). This clone is characterized, among other genetic traits (DiRienzo et al, 1994;Haubek et al, 1996;Hayashida et al, 2002), by enhanced leukotoxin production because of a 530-base-pair (bp) deletion in the promoter region of the leukotoxin gene operon (Brogan et al, 1994). Cross-sectional studies show that it is associated with disease in individuals of African descent, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…a particular clone, termed JP2, of Aggregatibacter [formerly Actinobacillus (Nørskov-Lauritsen & ] actinomycetemcomitans which, like traditional pathogens, may be isolated from multiple patients in geographically distinct areas (Haubek et al, 2008). This clone is characterized, among other genetic traits (DiRienzo et al, 1994;Haubek et al, 1996;Hayashida et al, 2002), by enhanced leukotoxin production because of a 530-base-pair (bp) deletion in the promoter region of the leukotoxin gene operon (Brogan et al, 1994). Cross-sectional studies show that it is associated with disease in individuals of African descent, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, bacterial species must be viewed as populations of clones about which it is impossible to generalize particularly with regard to pathogenic potential. Recent, yet limited information indicates that this applies to oral bacteria too (DiRienzo et al 1994, Chen et al 2004, Kilian et al 2006, Haubek et al 2007, Kato et al 2007, Tachibana-Ono et al 2008, Inaba et al 2008.…”
mentioning
confidence: 99%
“…Furthermore, the correlation of different serotypes with various periodontal conditions remains unclear. Data in the literature have consistently shown that serotype b is detected more frequently in localized aggressive periodontitis (LAgP) patients, mainly of African origin (Newman et al 1976, Slots 1976, Newman & Socransky 1977, DiRienzo et al 1994, Haubek et al 1997, serotype a can be isolated from chronic periodontitis lesions in American subjects (Zambon et al 1983a), while in Northern Europe the three serotypes are equally represented and serotype c may be more prevalent in periodontal health , Haubek et al 1995. In contrast, in Japanese subjects periodontal disease appears to be associated mainly with serotype c (Thiha et al 2007), while it has been reported that serotype b may not be associated with LAgP in Korean subjects (Chung et al 1989).…”
mentioning
confidence: 99%